Evaluasi Teknologi Produksi pada Sentra Industri Keripik Tempe Grobog Wonogiri - Agusti, Febrina; Wisudawati, Tri; Tri Risqi, Fajar; Kumaratunggadewi, Kumaratih (Duta Abdimas, 2022)
Evaluation of productivity and technological needs was an important process in a production process. It was used to assist maintenance and repairs in production. MSMEs at the Grobog Wonogiri tempe chips industrial center have used a slicing machine to slice the benguk seeds. The use of these machines causes problems, namely the results of the pieces do not match the needs that were wide but destroyed, besides on the other problems, machine was not environmentally friendly. The result of the implementation of the activity was an evaluation related to the technology used, so it can be seen the need for a machine that was suitable for the specifications of slicing koro benguk beans. So, it was expected to increase productivity.